Improving the LGBTQ2S+ cultural competency of healthcare trainees: advancing health professional education. - Matthew Lee (Canadian Medical Education Journal, 2020)
Background: Lesbian, Gay, Bisexual, Trans, Queer, and Two-spirit (LGBTQ2S+) populations experience worse health outcomes compared to age-matched heterosexual and cisgender peers. Health professionals’ deficient knowledge and negative attitudes can contribute to these inequities. Healthcare trainees report insufficient LGBTQS2+ cultural competence training.